Effects of elevated CO2 and cadmium stress on vegetable quality and cadmium accumulation - Xiao Wang; Deyan Li; Xiaohui Song (Horticultural Science)
The aim of this study was to determine the effects of elevated CO₂ (eCO2) on the quality and cadmium (Cd) accumulation of vegetables grown in soil with a background Cd level or in Cd-contaminated soil. We used four types of vegetable: pak choi (Brassica rapa L.), water spinach (Ipomoea aquatica Forssk.), cherry radish (Raphanus raphanistrum subsp. sativus (L.) Domin) and pepper (Capsicum annuum L.). Cd stress significantly reduced vegetable vitamin C and reducing sugar content; however, under eCO2, vitamin C and reducing sugar content levels were significantly higher than they were under ambient CO2 (aCO2) levels. The nitrate content of pak choi, cherry radish and pepper was reduced under eCO2, and the effect was more pronounced among plants grown under Cd stress. The Cd content of cherry radish and pepper roots grown under eCO2 and Cd stress was significantly reduced (29.2% and 18.5%, respectively) compared with plants grown under aCO2 conditions and Cd stress. The Cd transfer coefficient of pak choi and water spinach grown under eCO2 and Cd stress was significantly lower (22.7% and 25.2%, respectively) than under aCO2 conditions. Our data suggest that growing vegetables under eCO2 is beneficial, especially when grown in Cd-contaminated soil, because Cd accumulation is reduced and vegetable quality is improved.